Pengaruh Webiste Quality Dan Flashsale Terhadap Impulse Buying Pada Pengguna E-Commerce Blibli.Com Di Pulau Lombok - Khalda Fadila; Rusminah Rusminah; Hilmiati Hilmiati (Postgraduate, University of Mataram, 2023)
This study aims to determine the Effect of Website Quality (X1) and Flashsale (X2) on Impulse Buying in Blibli.com E-Commerce Users on Lombok Island. Respondents in this study amounted to 100 consumers. The type of research used is quantitative research with a causal associative approach. The data collection method uses a survey through a questionnaire. The analysis technique used is Multiple Linear Repression. The results of this study indicate that: (1) Website Quality has a positive and significant effect on Impulse Buying for Blibli.com E-Commerce Users on Lombok Island. (2) Flashsale has a positive and significant effect on Impulse Buying for Blibli.com E-commerce Users on Lombok Island